The Neuroprotection of Low-Dose Morphine in Cellular and Animal Models of Parkinson’s Disease Through Ameliorating Endoplasmic Reticulum (ER) Stress and Activating Autophagy - Wang, Bing; Su, Cun-Jin; Liu, Teng-Teng; Zhou, Yan; Feng, Yu; Huang, Ya; Liu, Xu; Wang, Zhi-Hong; Chen, Li-Hua; Luo, Wei-Feng; Liu, Tong (Frontiers in Molecular Neuroscience, 2018)
Parkinson’s disease (PD) is a common neurodegenerative disease characterized the progressive loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc). Brain endogenous morphine biosynthesis was reported to be impaired in PD patients and exogenous morphine attenuated 6-hydroxydopamine (6-OHDA)-induced cell death in vitro. However, the mechanisms underlying neuroprotection of morphine in PD are still unclear. In the present study, we investigated the neuroprotective effects of low-dose morphine in cellular and animal models of PD and the possible underlying mechanisms. Herein, we found 6-OHDA and rotenone decreased the mRNA expression of key enzymes involved in endogenous morphine biosynthesis in SH-SY5Y cells. Incubation of morphine prevented 6-OHDA-induced apoptosis, restored mitochondrial membrane potential, and inhibited the accumulation of intracellular reactive oxygen species (ROS) in SH-SY5Y cells. Furthermore, morphine attenuated the 6-OHDA-induced endoplasmic reticulum (ER) stress possible by activating autophagy in SH-SY5Y cells. Finally, oral application of low-dose morphine significantly improved midbrain tyrosine hydroxylase (TH) expression, decreased apomorphine-evoked rotation and attenuated pain hypersensitivity in a 6-OHDA-induced PD rat model, without the risks associated with morphine addiction. Feeding of low-dose morphine prolonged the lifespan and improved the motor function in several transgenic Drosophila PD models in gender, genotype, and dose-dependent manners. Overall, our results suggest that neuroprotection of low-dose morphine may be mediated by attenuating ER stress and oxidative stress, activating autophagy, and ameliorating mitochondrial function. Keywords: Morphine; Parkinson’s disease; Neuroprotection; Autophagy; ER stress